A novel fluorescent "OFF-ON" sensing strategy for Hg (II) in water based on functionalized gold nanoparticles. (September 2022) - Li, Gufeng; Lu, Mingrong; Li, Shaoqing; Yang, Min; Zhang, Yuanling; Zhang, Yanli; Wang, Hongbin; Yang, Wenrong
Abstract: Mercury ion (Hg 2+ ) is a heavy metal pollutant that can affect the safety of water environment and endanger human health. A novel detection strategy (GNPs-L -Cys-Rh6G2) for Hg 2+ based on a fluorescence "OFF-ON" was proposed. Gold nanoparticles (GNPs) were assembled with l -cysteine (L -Cys), which was used as a "bridge" to link with rhodamine 6G derivatives (Rh6G2). The fluorescence state transition of GNPs-L -Cys-Rh6G2 switching from "OFF"-"ON" was observed because Hg 2+ opened the spirolactam ring through a catalytic hydrolysis mechanism. The fluorescence signal of the GNPs-L -Cys-Rh6G2 system mixed with Hg 2+ in the concentration range of 10–100 μM was analyzed and determined with a limit of detection (LOD) of 2 μM ( S/N  = 3). Moreover, the spiked Hg 2+ concentration in real water samples were successfully quantified by GNPs-L -Cys-Rh6G2, which was in line with the ideal average recovery rate and relative standard deviation. The proposed strategy exhibited high specificity, sensitivity and stability, providing a novel sensing platform for heavy metal ions detection in water environment. Graphical abstract: Image 1 Highlights: The proposed strategy provides a novel sensing platform for heavy metal ions analysis based on GNPs. The GNPs-L -Cys-Rh6G2 was prepared via self-assembling GNPs using L -Cys and Rh6G2 as functional molecules. The GNPs-L -Cys-Rh6G2 shows a low LOD of 2 μM ( S/N = 3) for Hg 2+ .